REFLEKSYJNA PRAKTYKA W NAUCZANIU JĘZYKA SPECJALISTYCZNEGO - Gajewska, Elżbieta; Sowa, Magdalena (Neofilolog, 2019)
Compared to colleagues teaching foreign languages for general purposes, who can use ready-made syllabuses or programs, the LSP teacher has to reflect on methodology at the level of course planning. The scope and nature of the proposed course content is tailored to the specific needs of a student. The analysis of these needs is based on interviews and questionnaires. There are many examples of such tools, but none of them are universal or exhaustive, nor can they be. The purpose of this article is to propose a set of parameters to facilitate investigation of the educational context, which could be a starting point for the development of questionnaires tailored to specific education needs.